Chair-Based Exercise Interventions for Nursing Home Residents: A Systematic Review - Cordes, Thomas; Schöne, Daniel; Kemmler, Wolfgang; Wollesen, Bettina (Journal of the American Medical Directors Association, 2020)
Objectives: Despite mobility impairments, many residents have physical, cognitive, and psychosocial resources that should be promoted. The aim was to summarize the current evidence on chair-based exercise (CBE) interventions for nursing home residents. Design: Systematic review registered with Prospero (registration number: CRD42018078196). Setting and Participants: Nursing home residents in long-term care. Methods: Five electronic databases were searched (MEDLINE, Embase, CINAHL, Cochrane Central, and PsycINFO) from inception until July 2020. Title, abstract, and full-text screening as well as quality assessment with the Downs and Black checklist was done by 2 independent reviewers. Studies were eligible if they (1) were conducted in nursing home residents, (2) included participants with a mean age of 65 years, (3) had at least 1 treatment arm with seated exercises only, (4) included active or inactive controls, (5) measured outcomes related to physical and/or cognitive functioning and/or well-being, and (6) controlled studies or single-group pre-post design. Because of a heterogeneity in characteristics of included studies, we refrained from conducting a meta-analysis. Results: Ten studies met the inclusion criteria (n = 511, mean age 79 ± 7 years, 65% female). Studies differed in sample size (12-114) as well as in training type (multicomponent, Yoga/Qigong/breathing exercise, range of motion) and dose (frequency 2 sessions/week to daily, intensity low to moderate, time 20-60 minutes/session, 6 weeks to 6 months). Overall, CBE appears to be feasible and safe. Studies found task-specific improvements in physical and cognitive functions and enhanced well-being. Three studies demonstrated improved lower body performance following a multicomponent CBE program in mobile residents. Three studies only including residents unable to walk reported improved physical functions, indicating that immobile residents benefit from CBE programs. There was a lack of separating mobile and immobile residents in analyses. Conclusions and Implications: The results indicate that CBE interventions may improve physical and cognitive functions as well as well-being in nursing home residents. Task-specific multicomponent CBE appears to be best for improving different domains of physical and cognitive functioning. More high-quality trials are needed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: chair-based; exercise; intervention; Nursing home; physical function